2017
DOI: 10.1016/j.bbadis.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Metformin ameliorates gender-and age-dependent hemodynamic instability and myocardial injury in murine hemorrhagic shock

Abstract: Severity of multiple organ failure is significantly impacted by age and gender in patients with hemorrhagic shock. However, the molecular mechanisms underlying the enhanced organ injury are not fully understood. AMP-activated protein kinase (AMPK) is a pivotal orchestrator of metabolic responses during stress. We investigated whether hemorrhage-induced myocardial injury is age and gender dependent and whether treatment with metformin, an AMPK activator, affords cardioprotective effects. C57/BL6 young (3–5 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…We have previously shown that pharmacological activation of AMPK with a synthetic AMP monolog AICAR can exert lung and cardiac protective effects and improve the hemodynamic compensatory mechanisms in a murine hemorrhagic shock model (8, 9). Similarly, we have previously described that treatment with metformin ameliorates myocardial damage in middle-aged (9–12 months old) mice subjected to severe hemorrhage (23). Conversely, in this study, we demonstrated that absence of AMPKα1 in genetically deficient mice worsened the hemodynamic instability, the systemic inflammatory response, and the liver and lung injury after hemorrhagic shock when compared to mice with a functional AMPKα1, thus suggesting that AMPKα1 is an important requisite for regulating the metabolic response as well as the hemodynamic performance during hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 52%
“…We have previously shown that pharmacological activation of AMPK with a synthetic AMP monolog AICAR can exert lung and cardiac protective effects and improve the hemodynamic compensatory mechanisms in a murine hemorrhagic shock model (8, 9). Similarly, we have previously described that treatment with metformin ameliorates myocardial damage in middle-aged (9–12 months old) mice subjected to severe hemorrhage (23). Conversely, in this study, we demonstrated that absence of AMPKα1 in genetically deficient mice worsened the hemodynamic instability, the systemic inflammatory response, and the liver and lung injury after hemorrhagic shock when compared to mice with a functional AMPKα1, thus suggesting that AMPKα1 is an important requisite for regulating the metabolic response as well as the hemodynamic performance during hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 52%
“…Metformin effect on these cytokines, particularly for TNF-α [25]. Our findings of a strong response to metformin in Covid-19 suggest that TNF-α reduction may be the primary way by which metformin reduced mortality from Covid-19.…”
Section: Discussionmentioning
confidence: 62%
“…AMPK activation leads to the activation of peroxisome proliferator-activated receptor γ co-activator α (PGC-1α). Previous studies have indicated that mitochondrial dysfunction is a result of low AMPK activation (8). The release of HMGB1 by necrotic cells raises the level of inflammatory activity.…”
Section: Anti-inflammatory Mechanism Of Metforminmentioning
confidence: 99%